Sustainable Use and Development of Watersheds - Gönenç, I.E. (Springer, 2017)
John Wesley Powell, U.S. scientist and geographer, put it best when he said that a watershed is: …that area of land, a bounded hydrologic system, within which all living things are inextricably linked by their common water course and where, as humans settled, simple logic demanded that they become part of a community. Watersheds come in all shapes and sizes. They cross sectorial boundaries (e.g. county, state/province, and country). No matter where you are, you are in a watershed! World-wide, watersheds supply drinking water, provide r- reation and respite, and sustain life. Watersheds are rich in natural capital, producing goods (agriculture and fisheries products) and services (industry and technology) for broad geographic areas. In many countries, at the base of watersheds where tributaries empty into large water-bodies (e.g. estuaries, seas, oceans) are centers of society and are typically densely populated areas. These areas serve as concentrated centers of the socio-economic system. They also are centers of domestic and international trade, tourism, and c- merce as well as the center of governments (capitals) where local, regional and national legislatures are located. As we all live in a watershed, our individual actions can directly affect it. The cumulative effects of all the individual actions of everyone within a watershed may be, and often are devastating to the quality of water resources and affect the health of living things including humans. Therefore, watershed systems are highly subject to threat to human security and peace.